Archaeal ribosomal stalk protein interacts with translation factors in a nucleotide-independent manner via its conserved C terminus - Nomura, Naoko (National Academy of Sciences, 2012)
Protein synthesis on the ribosome requires translational GTPase factors to bind to the ribosome in the GTP-bound form, take individual actions that are coupled with GTP hydrolysis, and dissociate, usually in the GDP-bound form. The multiple copies of the flexible ribosomal stalk protein play an important role in these processes. Using biochemical approaches and the stalk protein from a hyperthermophilic archaeon, Pyrococcus horikoshii, we here provide evidence that the conserved C terminus of the stalk protein aP1 binds directly to domain I of the elongation factor aEF-2, irrespective of whether aEF-2 is bound to GTP or GDP. Site-directed mutagenesis revealed that four hydrophobic amino acids at the C terminus of aP1, Leu-100, 103, 106, and Phe-107, are crucial for the direct binding. P1 was also found to bind to the initiation factor aIF5B, as well as aEF-1α, but not aIF2γ, via its C terminus. Moreover, analytical ultracentrifugation and gel mobility shift analyses showed that a heptameric complex of aP1 and aP0, aP0(aP1)(2)(aP1)(2)(aP1)(2), can bind multiple aEF-2 molecules simultaneously, which suggests that individual copies of the stalk protein are accessible to the factor. The functional significance of the C terminus of the stalk protein was also shown using the eukaryotic proteins P1/P2 and P0. It is likely that the conserved C terminus of the stalk proteins of archaea and eukaryotes can bind to translation factors both before and after GTP hydrolysis. This consistent binding ability of the stalk protein may contribute to maintaining high concentrations of translation factors around the ribosome, thus promoting translational efficiency.